2004
DOI: 10.1098/rspb.2003.2577
|View full text |Cite
|
Sign up to set email alerts
|

A novel test of the phenotype–linked fertility hypothesis reveals independent components of fertility

Abstract: The phenotype-linked fertility hypothesis predicts that male sexual ornaments signal fertilizing efficiency and that the coevolution of male ornaments and female preference for such ornaments is driven by female pursuit of fertility benefits. In addition, directional testicular asymmetry frequently observed in birds has been suggested to reflect fertilizing efficiency and to covary with ornament expression. However, the idea of a phenotypic relationship between male ornaments and fertilizing efficiency is ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 82 publications
(89 reference statements)
0
46
0
Order By: Relevance
“…A positive relationship between comb size and sperm quality seemed to be strain specific (Gebriel et al, 2009;El Ghany et al, 2011;Udeh et al, 2011). Some studies reported no relationship between comb size and sperm quality (Pizzari et al, 2004;Bilcik and Estevez, 2005;Baczynski, 2008;Prieto et al, 2011), while others reported a negative relationship between comb size and sperm movement (Parker et al, 2006;Navara et al, 2012).…”
Section: Comb and Wattles Characteristicsmentioning
confidence: 99%
“…A positive relationship between comb size and sperm quality seemed to be strain specific (Gebriel et al, 2009;El Ghany et al, 2011;Udeh et al, 2011). Some studies reported no relationship between comb size and sperm quality (Pizzari et al, 2004;Bilcik and Estevez, 2005;Baczynski, 2008;Prieto et al, 2011), while others reported a negative relationship between comb size and sperm movement (Parker et al, 2006;Navara et al, 2012).…”
Section: Comb and Wattles Characteristicsmentioning
confidence: 99%
“…We also recorded the number of sperm cells detected by the CASA plug-in because moving sperm are likely to interfere more with each other at higher densities, a parameter we could not control. Sperm velocity has previously been described using VSL, VAP, or VCL or a combination of these parameters (Holt et al 1997;Froman and Feltmann 2000;Gage et al 2004;Pizzari et al 2004). In our samples, these parameters were strongly correlated with each other (r, 0.93-0.998; all P<0.0001).…”
Section: Sperm Velocity and Sperm Longevitymentioning
confidence: 99%
“…Birkhead & Fletcher 1995;Parker et al 2006). Furthermore, these traits do not inevitably translate into an increased fertilizing efficiency (Pizzari et al 2004;Pilastro et al 2008); thus, actual fecundity benefits for the selective females have only rarely been demonstrated (Wagner & Harper 2003;Malo et al 2005a,b;Rogers et al 2008).…”
Section: Introductionmentioning
confidence: 99%